THE EFFECTIVENESS OF VIRTUAL REALITY LEARNING MEDIA BASED ON CANDI KEDATON MUARA JAMBI IN ENHANCING HISTORICAL AWARENESS OF SENIOR HIGH SCHOOL STUDENTS AT SMA PANGUDI LUHUR SEDAYU: Efektivitas Media Pembelajaran Virtual Reality Berbasis Candi Kedaton Muara Jambi dalam Meningkatkan Kesadaran Sejarah Siswa SMA Pangudi Luhur Sedayu - Rufer Firma Harianja Rufer; muh. akbar; Boni Marian (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
History learning in Indonesian senior high schools faces a paradox in which the curriculum mandates the formation of historical awareness while classroom practice still relies on conventional methods such as textbooks, slide presentations, and online videos. Local heritage sites that could anchor meaningful learning often remain geographically inaccessible to most students. This study addresses that gap by examining the effectiveness of a virtual reality learning medium based on Candi Kedaton Muara Jambi in enhancing the historical awareness of tenth-grade students at SMA Pangudi Luhur Sedayu. A 360-degree video integrated with virtual reality was developed using a Research and Development approach with the ADDIE model and was validated by media and content experts. The product was implemented through a quasi-experimental design involving 64 students divided into experimental and control classes of 32 students each. Historical awareness data were collected using a closed-ended questionnaire administered as pre-test and post-test, and the data were analysed using SPSS 25 with Kolmogorov-Smirnov, Levene, paired-sample t-test, and independent-sample t-test. The findings indicate that the experimental class improved from a mean of 75.83 to 84.91 while the control class moved from 74.96 to 78.53. The independent-sample t-test produced a significance value of 0.000, confirming that the virtual reality medium has a statistically significant effect on historical awareness. The novelty of this study lies in connecting students directly with a specific Hindu-Buddhist site located outside Java through immersive technology, focusing measurement on the affective construct of historical awareness, and providing strong empirical support through a rigorous quasi-experimental design.